Bringing back the ‘soul’ to STEM - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
MANY years ago, Akademik Sains Malaysia organised a timely conference themed “Injecting the soul in R&D” in Kuching.